PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DAN MEDIASI KEBIJAKAN DIVIDEN - Mochamad Umar Mai (Politeknik Negeri Jakarta, 2011)
This study aims to determine and analyze 1) the influence of corporate governance mechanisms on dividend policy and value of the firm; 2) the effects of dividend policy mediated in order of causality between corporate governance mechanisms and value of the firm. The sample used was the manufacturing companies listed in Indonesia Stock Exchange with the observation period starting in 2000 to 2007. The results showed that: 1) corporate governance mechanisms in istitutional ownership represented by institutional ownership have a positive and significant impact on dividend policy represented by dividend payout ratio; 2) corporate governance mechanisms are represented by institutional ownership, independent boards, and board’s size have a positive effect and significant impact on dividend policy, represented by Tobin's q; and 3) the dividend policy does not mediate the relationship of causality between corporate governance mechanisms (which are represented by boards institutional ownership and board’s size) with Tobin's q. Key Word : corporate governance mechanism, value of the firm, boards independent, dividend payout ra